2013
DOI: 10.18438/b82g7v
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the MISO Data: Broader Perspectives on Library and Computing Trends

Abstract: Objective – To analyze data collected by 38 colleges and universities that participated in the Measuring Information Services Outcomes (MISO) survey between 2005 and 2010. Methods – The MISO survey is a Web-based quantitative survey designed to measure how faculty, students, and staff view library and computing services in higher education. Since 2005, over 10,000 faculty, 18,000 students, and 15,000 staff have completed the survey. To date, the MISO survey team has analyzed the data by faculty ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Assessing students' needs on the library website is critical for academic libraries: "Library websites are a gateway to library resources, services, contact information, and events" (Anderson, 2016, p. 19). While previous studies show that usage of library websites has declined over time (Allen, Baker, Wilson, Creamer & Consiglio, 2013;Anderson, 2016), libraries continue to improve their websites for students' use. Mierzecka and Suminas (2017) examined which features of the library website are most important for students at the University of Warsaw in Poland and the Vilnius University in Lithuania via open-ended responses.…”
Section: Patterns Of Students' Library Experiencementioning
confidence: 97%
“…Assessing students' needs on the library website is critical for academic libraries: "Library websites are a gateway to library resources, services, contact information, and events" (Anderson, 2016, p. 19). While previous studies show that usage of library websites has declined over time (Allen, Baker, Wilson, Creamer & Consiglio, 2013;Anderson, 2016), libraries continue to improve their websites for students' use. Mierzecka and Suminas (2017) examined which features of the library website are most important for students at the University of Warsaw in Poland and the Vilnius University in Lithuania via open-ended responses.…”
Section: Patterns Of Students' Library Experiencementioning
confidence: 97%
“…Additional studies that analyzed large aggregate data sets suggested that faculty value and use the academic libraries' physical spaces less than students (Allen, Baker, Wilson, Creamer & Consiglio, 2013;Baker, et al, 2018;Thompson, Kyrillidou & Cook, 2008). For instance, two studies examined Measuring Information Services Outcomes (MISO) data for several U.S. based colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study from OCLC shows such a decrease among college students, from 61% in 2005 to 57% in 2010, although 22% of students who do use the website use it at least weekly, an increase of 7% over 2005(De Rosa, Cantrell, Carlson, Gallagher, Hawk, & Sturtz, 2010. The Measuring Information Services Outcomes (MISO) survey found a decrease in student usage of library websites between 2008 and 2010 (Allen, Baker, Wilson, Creamer, & Consiglio, 2013). Wood and Walther (2000) reminds us that, although there is a wealth of free information on the Internet, the profit motive remains strong for publishers, and patrons will need libraries to receive free access to subscription material.…”
Section: Literature Reviewmentioning
confidence: 99%